Is tax harmonization useful? - Wolfgang Eggert; Bernd Genser (University of Konstanz, Center of Finance and Econometrics (CoFE), 2000)
It is a widely acknowledged result of the literature on capital tax competition that underprovision of public goods can only be avoided if tax coordination between governments is intensive and residence-based capital taxation can be enforced. In this paper we use a model where commodity and factor taxes are available and we show that governments competing for tax bases will choose a globally efficient tax structure. In contrast to previous conclusions, we also show that the availability of a destination-based commodity tax or a labor tax is necessary to mitigate the problem of inefficient Nash equilibria and thus reduces the necessity of supranational tax harmonization or coordination.
urn:nbn:de:bsz:352-opus-5284
Keywords: 330; Steuerwettbewerb; Steuerharmonisierung; Doppelbesteuerung; Zwei-Länder-Modell; Nash-Gleichgewicht; Theorie; Bestimmungslandprinzip